Hydrographic Requirements for Planning and Development in African Coastal and Inland Waters - International Hydrographic Bureau (The International Hydrographic Review, 2015)
Hydrography involves collecting data about the depth of water, the position of submerged dangers to navigation and the movement of water in the world’s continental shelves and oceans, and publishing such data in the form of nautical charts. Such charts are essential for the safety of passengers and cargoes, for the exploration and exploitation of marine resources and the protection of marine environment. The latest charts available off the coasts and in the inland navigable waters of Africa are very often based on data collected up to 150 years ago. There are only five hydrographic ships and 13 hydrographic launches to survey 10,250,000 km2 of African countries’ Exclusive Economic Zones; only seven African maritime countries have any capability to produce their own nautical charts. In order to start to improve this highly undesirable restraint on the African economy, it is suggested that each African maritime country should form a national Hydrographic Committee and seek expert advice on creating a national hydrographic capability. It is also suggested that three Regional Hydrographic Centres should be established, attached to existing Regional Centres in East, West and North Africa, to provide on-going advice within the Region and to undertake the maintenance of the highly specialized hydrographic surveying equipment needed and the training of nautical cartography. The International Hydrographic Organization is willing to provide advice on the development of these facilities.